Infrared and Microwave Radiometry as A Means of Thermodynamic State Remote Control of Atmospheric Boundary Layer - Velichko, A.P.; Osrovsky, E.V.; Mirsaitov, S.F.; Snedkov, A.B. (International Journal of Engineering and Technology, 2018)
In the present research an attempt was made to extract information obtained on the basis of IR radiometric measurements in order to determine content of moisture and aerosol in the atmosphere, as well as height of the cloud base. Particular attention was paid to the method of measurement and processing and presentation of the results.